PERANAN ECONOMIC ORDER QUANTITY (EOQ) DAN JUST IN TIME (JIT) DALAM PENGENDALIAN PERSEDIAAN PADA UD.RISMA JATI MANDIRI - Hasanah, Deviatul; Hwihanus, Hwihanus (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTThe research objective is to see the ordering of raw materials at UD. Risma Jati Mandiri can be applied to the EOQ and JIT methods. The results are analyzed and compared using two inventory systems, namely EOQ and JIT to minimize the total cost of inventory and the risk of loss from inventory procurement. Descriptive quantitative approach is the method used in this study. Meanwhile, the data collection techniques used were field studies and literature studies. The EOQ formula, safety stock, reorder, and JIT formula are the data analysis techniques used. The results obtained from the research prove that the EOQ formula and the JIT formula can work appropriately and efficiently than the policies carried out by UD. Risma Jati Mandiri. Between the EOQ and JIT methods, the JIT method has greater efficiency when viewed from the amount of the total cost of raw material inventory and the amount of cost savings, so as to minimize inventory costs and the risk of loss due to the procurement of raw materials, when compared to the company's total inventory costs.